INTELLIGENT AUTOMATION - USES, BENEFITS, AND IMPACT - Bipasha Rajkhowa, Sujata Joshi, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Digital Transformation has necessitated massive transition in operating regimes of businesses resulting in the adoption of upcoming technologies to extract optimum productivity. Intelligent automation, a combination of artificial intelligence and Robotic Process Automation is not just capable of automating repetitive, structured processes but also process unstructured data and provide with accurate predictions based on the analysis. However, not much exploration is conducted in the domain of intelligent automation and its contribution to the various sectors such as banking, insurance, healthcare, etc. Hence the objective of this study is to explore and understand the uses and benefits and impact of intelligent automation across different industries. A case study approach has been adopted for this research wherein firstly various use cases of intelligent automation are studied and then we outlined how intelligent automation can help in smooth operations reducing human intervention and improving accuracy in business forecasts for future applications